Cardiac Defibrillation - Erkapic, Damir; Bauernfeind, Tamas (IntechOpen, 2013)
Sudden cardiac death and ventricular arrhythmia play a prominent role in mortality in our era. One of the biggest milestones in the therapy of ventricular arrhythmias was the invention of cardiac defibrillation. There were several important developments in the last decades, making nowadays automated external and internal defibrillators widely available. However, the rapid evolution and high differentiation of available options presents a challenge to be kept "up-to-date". With this book, we would like to review the actual guidelines and give practical advices concerning of indications in cardiomyopathy patients, possible contraindications and complications, the perioperative management including anticoagulation and antibiotics, and the programming and follow-up of defibrillator devices.